2002
DOI: 10.1017/s1355838202015029
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in RRM4 uncouple the splicing repression and RNA-binding activities of polypyrimidine tract binding protein

Abstract: The polypyrimidine tract binding protein (PTB, or hnRNP I) contains four RNA-binding domains of the ribonucleoprotein fold type (RRMs 1, 2, 3, and 4), and mediates the negative regulation of alternative splicing through sequencespecific binding to intronic splicing repressor elements. To assess the roles of individual RRM domains in splicing repression, a neural-specific splicing extract was used to screen for loss-of-function mutations that fail to switch splicing from the neural to nonneural pathway. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 32 publications
5
45
0
Order By: Relevance
“…As a splicing factor, PTB has been shown to repress exon inclusion in a number of genes and, thus, induce exon skipping. Genes regulated negatively by PTB in pre-mRNA splicing include ␣-and ␤-tropomyosin (33-35), FGF-R1 (36), FGF-R2 (37,38), c-src (39), GABA␥2 (40), fibronectin (41), caspase-2 (42), and ␣-actinin (43). Our results suggest that the MRP1 gene could be another target regulated by PTB.…”
Section: Positionmentioning
confidence: 84%
“…As a splicing factor, PTB has been shown to repress exon inclusion in a number of genes and, thus, induce exon skipping. Genes regulated negatively by PTB in pre-mRNA splicing include ␣-and ␤-tropomyosin (33-35), FGF-R1 (36), FGF-R2 (37,38), c-src (39), GABA␥2 (40), fibronectin (41), caspase-2 (42), and ␣-actinin (43). Our results suggest that the MRP1 gene could be another target regulated by PTB.…”
Section: Positionmentioning
confidence: 84%
“…The distribution of PTB binding sites within introns has led to several proposed models of PTB action. For example, PTB could interfere with spliceosome assembly by binding to the branch point pyrimidine tract and therefore directly sequestering the branch-point or competing with U2AF, an essential component of the constitutive splicing machinery [2,15,22,32]. In most cases, however, the exons silenced by PTB are flanked by PTB binding sites on both adjacent introns, and mutations of upstream PTB binding sequences have been shown to reduce binding of PTB to the downstream sites [7].…”
Section: The Many Functions Of Polypyrimidine Tract Binding Proteinmentioning
confidence: 99%
“…65,2008 Review Article 521 to function through an interaction with PTB, and might facilitate the identification of novel PTB targets. For example, many studies identified PTB binding sites by boundary analyses, gel shift experiments and cross-linking [10,15,22,32]. In light of the complex structures [85], these findings can be more easily interpreted.…”
Section: How Can the Ptb Structures Explain Its Multiple Functionsmentioning
confidence: 99%
“…One such repressor is the abundant polypyrimidine tract binding protein (PTB), a well-studied member of the hnRNP family (Perez et al 1997a;Liu et al 2002;Shen et al 2004;Wollerton et al 2004;Amir-Ahmady et al 2005;Sharma et al 2005;Spellman and Smith 2006;Boutz et al 2007;Matlin et al 2007;Sawicka et al 2008). The simplest model of PTB-mediated silencing is through competition with U2AF65 for the binding of the polypyrimidine tract (Singh et al 1995;Liu et al 2002;Sauliere et al 2006;Matlin et al 2007).…”
Section: Introductionmentioning
confidence: 99%